MEDIASI PERILAKU PENGELOLAAN KEUANGAN DALAM PENGARUH FINTECH DAN LITERASI KEUANGAN TERHADAP KINERJA USAHA - Muhamad Aditya Yulianto; Maria Rio Rita (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
This study aims to analyze the effect of financial literacy and financial technology (fintech) on business performance mediated by financial management behavior. This study uses a quantitative research design using partial least squares (PLS) based on covariance and Sobel test for mediation. Data is collected through distributing questionnaires either online and offline “Pojok Bayar” users that spread across the city of Salatiga. The population is “Ayo SRC” users application while the sample was selected using a purposive sampling. The number of research samples used is 100 people. First result of the study show that fintech has a significant positive effect on business performance. Second, financial literacy also has a significant positive effect on business performance. third, financial management behavior has a significant positive effect on business performance. Furthermore, the fourth and fifth hypotheses prove that fintech and financial literacy have a significant positive effect on financial management behavior. The sixth and seventh hypotheses are proven that financial management behavior mediates the effect of fintech and financial literacy on business performance. These finding shows that by using fintech and increasing financial literacy along with a good financial management behavior in business is able to maximize business performance. The researcher proposes an agenda for future research to consider the effects of sociodemographic variables and business characteristics in order to obtain a more comprehensive perspective on business performance.s.